2017
DOI: 10.1007/s00586-017-5229-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose reduction in thoracic and lumbar spine instrumentation using navigation based on an intraoperative cone beam CT imaging system: a prospective randomized clinical trial

Abstract: This study emphasizes the paramount importance of using low-dose protocols for intraoperative cone beam CT imaging coupled with the navigation system, as it at least does not affect the accuracy of pedicle screw placement and irradiates drastically less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Next, intraoperative medical procedure exposure to X-rays remains a problem. Intraoperative CT combined with a navigation system may be useful in improving the efficiency of the surgery and reducing the exposure of medical workers (22,23). In our experience, some key points should be considered in performing Endo-TLIF.…”
Section: Discussionmentioning
confidence: 93%
“…Next, intraoperative medical procedure exposure to X-rays remains a problem. Intraoperative CT combined with a navigation system may be useful in improving the efficiency of the surgery and reducing the exposure of medical workers (22,23). In our experience, some key points should be considered in performing Endo-TLIF.…”
Section: Discussionmentioning
confidence: 93%
“…It should be noted though that low-dose, ALARA protocols have been shown to be able to reduce the amount of radiation by up to a factor of 5 when compared to normal, high-dose protocols [14], and therefore are viable options in facilities where image enhancement is not available.…”
Section: Discussionmentioning
confidence: 99%
“…The planning information gives the orthopaedic doctor operation examination prompts. Two systems 80,127 have achieved a breakthrough in preoperative planning for THR surgery and can design prostheses for specific patients. In terms of preoperative planning for THA, the advantage of one system 92 is that it can automatically determine the key space parameters for the acetabulum before the operation so that it is more convenient to design the acetabulum prosthesis for special patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that the combination of spinal navigation and an intraoperative 3D perspective may overcome this shortcoming. 135,110,116,126,127 Villard et al 108 compared the radiation exposure of orthopaedic surgeons and 21 patients who underwent posterior lumbar internal fixation (10 cases with navigation and 11 hands‐on procedures). The plastic surgeon performing the PSP received 9.96 times the radiation received during an operation with a navigational system.…”
Section: Computer‐assisted Orthopaedic Surgery Navigation Systemsmentioning
confidence: 99%